Sociocultural Factors Affecting Vocabulary Development in Young South African Children - Southwood, Frenette; White, Michelle J.; Brookes, Heather; Pascoe, Michelle; Ndhambi, Mikateko; Yalala, Sefela; Mahura, Olebeng; Mössmer, Martin; Oosthuizen, Helena; Brink, Nina; Alcock, Katie (Frontiers in Psychology, 2021)
Sociocultural influences on the development of child language skills have been widely studied, but the majority of the research findings were generated in Northern contexts. The current crosslinguistic, multisite study is the first of its kind in South Africa, considering the influence of a range of individual and sociocultural factors on expressive vocabulary size of young children. Caregivers of toddlers aged 16 to 32 months acquiring Afrikaans (n=110), isiXhosa (n=115), South African English (n=105), or Xitsonga (n=98) as home language completed a family background questionnaire and the MacArthur-Bates Communicative Development Inventory (CDI) about their children. Based on a revised version of Bronfenbrenner’s (1977) ecological systems theory, information was obtained from the family background questionnaire on individual factors (the child’s age and sex), microsystem-related factors (the number of other children and number of adults in the child’s household, maternal level of education, and SES), and exosystem-related factors (home language and geographic area, namely rural or urban). All sociocultural and individual factors combined explained 25% of the variance in expressive vocabulary size. Partial correlations between these sociocultural factors and the toddlers’ expressive vocabulary scores on 10 semantic domains yielded important insights into the impact of geographic area on the nature and size of children’s expressive vocabulary. Unlike in previous studies, maternal level of education and SES did not play a significant role in predicting children’s expressive vocabulary scores. These results indicate that there exists an interplay of sociocultural and individual influences on vocabulary development that requires a more complex ecological model of language development to understand the interaction between various sociocultural factors in diverse contexts,